1979
DOI: 10.1021/ja00517a005
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects on strain energies

Abstract: Ab initio calculations employing the STO-3G basis set have been performed on numerous substituted derivatives of the strained (or unsaturated) molecules ethylene, cyclopropane, cyclobutane, acetylene, spiropentane, bicyclobutane, cyclopropane, tetrahedrane, and cubane. Substituents investigated include Li, BeH, BHa, BH3"", CH3, CH2"1", CH2~, CN, CF3, NH2, NH3+, OCH3, OH, O-, and F. Stabilization of strained molecules is achieved with -donating, ^-withdrawing, and most ir-donating substituents, withdrawal desta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(73 citation statements)
references
References 21 publications
2
71
0
Order By: Relevance
“…Also it was found that CT substituent is highly stabilizing as compared to radical and cation, probably because the O" substituent is a relatively strong a and n donor [56], which causes the cyclopropenyl anion to obtain aromatic character (6 n electrons), as compared to the radical (5 n electrons) and the cation (4 n electrons). For the electron withdrawing substituents such as CHO, CN and N0 2 , the stabilizing effect is more pronounced in the case of anion than in that of both radical and cation.…”
Section: Stabilization By Substituentsmentioning
confidence: 99%
“…Also it was found that CT substituent is highly stabilizing as compared to radical and cation, probably because the O" substituent is a relatively strong a and n donor [56], which causes the cyclopropenyl anion to obtain aromatic character (6 n electrons), as compared to the radical (5 n electrons) and the cation (4 n electrons). For the electron withdrawing substituents such as CHO, CN and N0 2 , the stabilizing effect is more pronounced in the case of anion than in that of both radical and cation.…”
Section: Stabilization By Substituentsmentioning
confidence: 99%
“…They characterized the microwave and infrared spectra of VA and EI two isomers, E-and Z-ethyleneimine in a temperature range from 150 to 900 °C and suggested a non-planar structure of vinylamine (CH 2 =CHNH 2 ) [1,2]. Moreover, theoretical studies on VA structure produced the same result [16,18,20,[56][57][58][59][60]. Traeger et.…”
Section: Introductionmentioning
confidence: 88%
“…Methylene is a ground state triplet (la), lying -10 kcal/mol below the singlet state (lb) (28). If the substituent X is a m--donor then, as in carbocations, the singlet structure is stabilised by donation into the "vacant" p-orbital on the carbene carbon.…”
Section: (B) Carbenesmentioning
confidence: 99%
“…T-Donating substituents are weakly stabilising in ethylene (28) but are strongly stabilising in a-X-ethyl cations (6), with the result that the proton affinities of alkenes H2C=CHX are larger for T-donors and are very substituent dependent (Table 4). The cyano group is weakly stabilising in acrylonitrile, HZC=CH(CN) (28), and is destabilising in CH7CH(CN)+ (6) and consequently the proton affinity of acrylonitrile is 18.2 kcal/mol less than that of ethylene. By comparison, in the protonation of singlet carbenes, both CHX and CH,Xi are strongly stabilised by T-donors and the proton affinities of the carbenes are therefore less substituent dependent than those of the ethylenes.…”
Section: (C) Proton Affinities Of Singlet Carbenesmentioning
confidence: 99%